Posttraumatic growth among adolescents victims of bullying: Posttraumatic growth pada remaja penyintas bullying - Cokorde Istri Ayu Laksmi Dewi; Tience Debora Valentina (Talenta Publisher, 2020)
Being a victim of bullying is a traumatic life event that may lead to various developmental problems among adolescents. Such a traumatic life event could negatively affect individuals’ emotional and physical well-being. However, for some individuals, traumatic life events could promote posttraumatic growth. The present paper describes posttraumatic growth among victims of bullying. Specifically, we describe some indicators and encouraging factors of posttraumatic growth among adolescents who had been victims of bullying. The present review can contribute to intervention programs to encourage posttraumatic growth among adolescents who had been victims of bullying. Menjadi korban bullying merupakan peristiwa kehidupan traumatis yang dapat menimbulkan berbagai masalah perkembangan di kalangan remaja. Peristiwa kehidupan traumatis semacam ini dapat berdampak negatif pada kesejahteraan emosional dan fisik individu. Namun, bagi sebagian individu, peristiwa kehidupan traumatis dapat mendorong posttraumatic growth. Makalah ini menjelaskan posttraumatic growth di antara korban bullying. Secara spesifik, kami menjabarkan beberapa indikator dan faktor pendorong posttraumatic growth di kalangan remaja yang pernah menjadi korban bullying. Ulasan ini dapat berkontribusi pada program intervensi untuk mendorong posttraumatic growth di antara remaja korban bullying.